Unveiling visitors’ delight in mangrove point park as an ecotourism spot: an analysis of activities and facilities satisfaction / Anastasia Marsha Lina Manisha Aminulrashid ... [et al.] - Aminulrashid, Anastasia Marsha Lina Manisha; Che Man, Shaibatul Islamiah; Nasir, Norji; Abdul Mutalib, Asilah; Ismail, Zalina (Universiti Teknologi MARA, Perak, 2024)
Mangrove Point Park in the Klang Islands Mangrove Forest Reserve stands as a testament to eco-tourism’s rejuvenating power. Once threatened by development, these mangroves have found a new life through the Selangor Maritime Gateway project. Since its opening in March 2023, the park has become a popular eco-tourism spot, offering various activities. This research aims to assess visitors’ satisfaction towards the existing activities and facilities at the site through a blend of qualitative and quantitative data collection methods. The study utilizes site inventory, observation, and a questionnaire survey to comprehensively evaluate the park’s offerings. It seeks to seamlessly incorporate the research's overarching objectives, which are (1) to identify the key activities and facilities currently provided, (2) to evaluate the expectation and performance gap in promoting the ecotourism industry, and (3) to examine visitors' satisfaction with the facilities and activities at Mangrove Point Park. The results of this study confirm that visitors are mostly dissatisfied with the provided activities and facilities, mainly on comfort and safety aspects, indicating the need for action to achieve higher visitors’ satisfaction.